1995
DOI: 10.1111/j.1472-765x.1995.tb01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Lecithinase reaction of Staphylococcus aureus strains of different origin on Baird-Parker medium

Abstract: Staphylococcus aureus produces one or more enzymes with lipolytic activity, but differences between strains have been reported (Owens and John 1975; O'Toole 1987; Rollof et al. 1987). The biological and biochemical properties of these enzymes have been investigated and results were recently reviewed (Kötting et al. 1984). Baird-Parker medium (Baird-Parker 1962) is a selective medium commonly used for the isolation of Staph. aureus. The presence of egg yolk in this medium permits the detection of two reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…The production of lecithinase was evaluated using Baird-Parker medium. The formation of an opaque halo around the colony indicated a positive result [31].…”
Section: Methodsmentioning
confidence: 99%
“…The production of lecithinase was evaluated using Baird-Parker medium. The formation of an opaque halo around the colony indicated a positive result [31].…”
Section: Methodsmentioning
confidence: 99%
“…This might indicate that staphylococci can catabolize surfactant lipids to some extent. The production and release of phospholipases by S. aureus has been described (24). LaForce et al (22) reported increased growth of S. aureus after incubation with complete natural rabbit surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…The production of lecithinase was evaluated using Baird-Parker medium. The formation of an opaque halo around the colony indicated a positive result [24]. …”
Section: Methodsmentioning
confidence: 99%